2020
DOI: 10.1177/0898264320972547
|View full text |Cite
|
Sign up to set email alerts
|

Are Positive Childhood Experiences Linked to Better Cognitive Functioning in Later Life?: Examining the Role of Life Course Pathways

Abstract: Objectives: We examine whether childhood family well-being is associated with cognitive functioning and to what extent the association between the family context and cognitive functioning is explained by adulthood resources. Methods: Data are drawn from the National Social Life, Health, and Aging Project Wave 3 (2015/2016; N = 3361). We measured cognitive functioning using the Montreal Cognitive Assessment. Childhood family factors included family-life happiness, family structure, and family socioeconomic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Contrary to ACEs, benevolent childhood experiences (BCEs) represent the positive experiences before 18 years, which do not depend on higher socioeconomic status in the family of origin. BCEs can not only provide a foundation for creating better family health in adulthood (Daines et al, 2021) but are also linked to various adult mental health outcomes, such as stress, depression (Bethell et al, 2019), forgiveness, family closeness (Crandall et al, 2019), post-traumatic stress disorder (PTSD) (Narayan et al, 2017;Karatzias et al, 2020), loneliness (Doom et al, 2021), and later life cognition (Lee and Schafer, 2021). BCEs were also significantly associated with adulthood insomnia among young adults (Geng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to ACEs, benevolent childhood experiences (BCEs) represent the positive experiences before 18 years, which do not depend on higher socioeconomic status in the family of origin. BCEs can not only provide a foundation for creating better family health in adulthood (Daines et al, 2021) but are also linked to various adult mental health outcomes, such as stress, depression (Bethell et al, 2019), forgiveness, family closeness (Crandall et al, 2019), post-traumatic stress disorder (PTSD) (Narayan et al, 2017;Karatzias et al, 2020), loneliness (Doom et al, 2021), and later life cognition (Lee and Schafer, 2021). BCEs were also significantly associated with adulthood insomnia among young adults (Geng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al, 2014 reported an elevated dementia risk among Chinese older adults who experienced the death of a parent early in life. Positive parent–child relationships and happy family dynamics were found to benefit cognitive functioning over time (Lee & Schafer, 2021). In terms of peer relations, research showed that children who lacked friends and felt lonely were at greater risk of developing poor adult health outcomes (Caspi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…African Americans are exposed to more traumatic experiences and stressors, such as discrimination and poverty, earlier on in life, which produces additional health risks and contributes to worse health outcomes in later life 45 , 46 . Although mental health disorders are not prevalent, the earlier emergence of multimorbidity could result from psychological distress at an earlier age 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of multiple combinations of four diseases suggest that patients present with complex disease profiles that have likely never been studied before. The level of social vulnerability of particular groups should also be considered, as a significant correlation between social vulnerability and the total number of chronic conditions was previously demonstrated, with depression/anxiety, obesity, and cardiovascular diseases being the most related 47 . Further, these diseases were present in many patterns for various racial groups.…”
Section: Discussionmentioning
confidence: 99%